ESCORT: Energy sweep compact rapid cycling hadron therapy. Issue 1 (April 2020) - Wah, Leo Kwee; Takayama, Ken; Adachi, Toshikazu; Kawakubo, Tadamichi; Dixit, Tanuja
Abstract: The Energy Sweep Compact Rapid Cycling Hadron driver for future cancer therapies based on the induction synchrotron concept is described. This fast cycling synchrotron that allows the energy sweep beam scanning. Assuming a 1.5 T bending magnet, the ring can deliver heavy ions of 430 MeV/u at 10 Hz. A beam fraction is dropped from the barrier bucket at the desired timing and the increasing negative momentum deviation of this beam fraction becomes enough large for the fraction to fall in the electrostatic septum extraction gap, which is placed at the large D(s) region. The programmed energy sweeping extraction makes spot scanning beam irradiation on a cancer area in depth possible.